ANALISA KECEPATAN SLUG ALIRAN DUA FASE DI DOWNSTREAM T-JUNCTION MINICHANNEL HORIZONTAL DENGAN RADIUS BELOKAN (r/dh) 0.7 - Untung Surya Dharma; Calista Anjani Dwiputri; Eko Nugroho; Asroni Asroni; Deendarlianto Deendarlianto; Indarto Indarto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Uneven distribution of the phases between in the main channel when two-phase flow passes through the T-junction it can cause the formation of slug flow which affects performance in the downstream area. The slug is formed due to the acceleration of the gas phase moving towards an average or stable velocity. The bend radius of the T-junction affects the formation of slug because the radius can increase the velocity of the gas phase. Research on the slug velocity was carried out in the downstream region of the horizontal mini channel T-junction. The working fluid used is air as the gas phase and water. The flow pattern and velocity slug analysis were carried out by visualizing the flow at a distance of ±30 mm from the T-junction, that works as a mixer of the working fluid. High-speed camera is used to record video and processed in the form of image processing with the MATLAB program. Two-phase flow slug velocity analysis conducted in the downstream area of ​​the horizontal minichannel T-junction, it can be concluded that the slug velocity tends to increase linearly with increasing superficial velocity of air and water. Comparison of slug velocity experimentally with the results of calculations using the equations of Fukano and Kariyasaki (1993) and Sudarja et al (2018) shows conformity with less than 10% of error margin, while Nicklin et al (1962) is ±30%.